KAJIAN PRAGMATIK KESANTUAN BERBAHASA ARAB PADA NOVEL KAUKAB AMUN KARYA SALLY MAGDI - Siti Aminah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
This article discusses the politeness in Arabic speech especially on the politeness strategies used by the characters in the novel Kaukab Amūn. By utilizing Brown and Levinson's view of politeness, it is concluded that in order for communication to be smooth and harmonious, speakers and hearer use positive and negative politeness strategies. The strategy of positive politeness that is done in order to maintain the proximity between the speaker and the hearer is realized in the form of avoiding conflict, involving the opponent in a certain activity/speaker activity, promising, giving praise, expressing jokes, giving attention and sympathy, using certain identity identifiers, asking approval, and showing optimism. The negative politeness strategy is done by using the indirect sentence, reducing the strength or the threat to the speech partner, using the apology expression, and paying respects to the hearer. In the dialogue between characters in the novel Kaukab Amūn face threatenings were found, both positive and negative face threathening and the characters use the face saving act strategies.